KARL POLANYI'S METACRITIQUE OF THE LIBERAL CREED Reading Polanyi's Social Theory in Terms of Dialectical Critical Realism - Despain, Hans G. (Journal of Critical Realism, 2011)
This paper interprets Karl Polanyi through dialectical critical realism. The paper maintains that this interpretation offers Polanyi methodological coherence and philosophical support. It further provides dialectical critical realism with an exemplar of explanatory critique. It is argued that the social theory of Polanyi aims at the demystification of market-systems as they are theoretically constructed by both orthodox and heterodox accounts of capitalism. Dialectical critical realism is best capable of situating the theoretical accomplishment of Polanyi's historical and dialectical critiques of social being.
Economics
Keywords: capitalism; critical realism; economic theory; economics; explanatory critique; liberal creed; neoliberalism; ontology; social history; social theory